2021
DOI: 10.3390/jcm10225238
|View full text |Cite
|
Sign up to set email alerts
|

Injuries during Laparoscopic Cholecystectomy: A Scoping Review of the Claims and Civil Action Judgements

Abstract: Background. To define what type of injuries are more frequently related to medicolegal claims and civil action judgments. Methods. We performed a scoping review on 14 studies and 2406 patients, analyzing medicolegal claims related to laparoscopic cholecystectomy injuries. We have focalized on three phases associated with claims: phase of care, location of injuries, type of injuries. Results. The most common phase of care associated with litigation was the improper intraoperative surgical performance (47.6% ± 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
(100 reference statements)
0
3
0
2
Order By: Relevance
“…Cirocchi et al showed that in many cases of malpractice claims and civil action suits, the patients’ morbidity and mortality were related to a misperception of the CVS, and not due to the surgeon’s negligence [ 47 ]. In such cases, stopping the procedure, taking time to reorientate the anatomical landmarks, or asking for help from a more experienced colleague would be the best options available [ 47 ]. Once again, factors related to patient safety and outcomes were considered fundamental compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Cirocchi et al showed that in many cases of malpractice claims and civil action suits, the patients’ morbidity and mortality were related to a misperception of the CVS, and not due to the surgeon’s negligence [ 47 ]. In such cases, stopping the procedure, taking time to reorientate the anatomical landmarks, or asking for help from a more experienced colleague would be the best options available [ 47 ]. Once again, factors related to patient safety and outcomes were considered fundamental compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of BDI not only increases the length of hospitalization and the economic burden, but also means that the patient is likely to face recurrent bile duct strictures, requiring secondary hepatectomy, biliary-enteric or hepato-enteric anastomosis, eventually leading to liver transplantation or death [ 14 , 15 ]. BDI is also a common cause of medicolegal problems for surgeons [ 16 ]. Therefore, in the procedure of difficult LC, we make the following recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of the use of monopolar diathermy is that there is a high risk of surrounding thermal damage. Slippage of clips off the cystic duct in relation to the gall bladder causes bile to spill into the surgical field and this invariably causes frequent instrument change which increases the risk of visceralrelated injuries [5,6].…”
Section: Introductionmentioning
confidence: 99%